Understanding success in private-public partnerships within Singapore’s preventive health sector: perspectives of private companies across various industries - Foo, Lai Jiet (2020)
Public-private partnership (PPP) has been gaining popularity around the world and has been utilized by governments for years to achieve many successful results for the society at large. While numerous studies have been conducted to understand the successes of PPP projects and their political performances to benefit the public, minimal emphasis has been dedicated to the private companies to understand their critical views of what success means to them, and what are the critical factors needed to drive those success for business performance. Therefore, the perspectives of private companies on PPP projects and their expectations on business performance should be uncovered further. Through a mixed-method approach, this management project hopes to contribute to the PPP literature and provide additional insights for future practitioners, to gain a better understanding on the perspectives of how private companies view PPP success, and their expectations of it.